PENGARUH JENIS PELARUT DAN METODE EKSTRAKSI TERHADAP AKTIVITAS ANTIBAKTERI DAN PENGHAMBATAN RADIKAL BEBAS EKSTRAK KULIT KAYU BANGKAL (Nauclea subdita) - Nazarni Rahmi; Rais Salim; Miyono; M. Ikhwan Rizki (BRIN Publishing, 2021)
Bangkal bark is one of the plant materials widely used by local people of South Borneo for medicine and beautycare. The limited research explores the extraction process and biological activity of bangkal bark for this use, especiallyfor acne treatment. This study was conducted to determine the difference of extraction methods and solvent polarity tophytochemical contents, antibacterial and radical scavenging activities of bangkal bark extracts. Bangkal bark wasextracted by maceration, percolation and soxhletation methods with various solvents, namely water, 96% ethanol, 70%ethanol and ethyl acetate. Total phenolic content by Folin ciocalteu, total flavonoids with AlCl3, and total tannins withvanillin were determined. Free radicals scavenging activity was determined with DPPH free radicals and antibacterialwith agar diffusion method. Soxhlet method with 96% ethanol solvent showed the highest phenolic content about81.12±1.66 mg/gr GAE. The highest flavonoid content was found on the percolation method with ethyl acetateabout 24.24± 0.057 mg/gr QE. Total tannin content was found on percolation methods with 96% ethanol about36.92±0.81 mg/gr CE. All of 70% ethanol extract showed high inhibitory strength of DPPH radical above 87%at a 1 mg/ml concentration. Antibacterial activity in the extract showed that all methods and solvents had inhibitoryproperties against P. acne with various inhibitory zones. In contrast, only ethyl acetate and water extracts were able toinhibit P. acne and S. aureus both.